Preparation of UO22+ as ion selective electrode depend on active substance 2+2Preparation of UOdibenzo-18-crown-6 (DB18C6) by using PVC polymer - Abbas noor Al-Sharify, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
A Uranyl (II) ion- selective electrode was prepared, depend on the active material Dibenzo-18-crown-6 ( DB18C6) as a sensor, deposed on a poly vinyl chloride  ( PVC) polymer, by using  Di-n-Octyl phenyl phthalate (DOPP) as a ,plasticizer substance in the membrane, the behavior and characteristics properties of this electrode have been studied.              It respond for the concentration range (1Ã—10-7-1Ã—10-1) mol/L of  uranyl ion with nernast linearity slope equal to 29 mV/decade of activity and correlation coefficient was about (0.9990).The selectivity coefficient of this electrode was calculated, in the presence of some interferencing cations and anions with certain uranyl (II) ion solutions.It was found that the range of pH response is (4-9), with response time (25) sec. at (298) K, and the electrode lifetime was found (28) days.